AN OVERVIEW OF FAIR AND FESTIVALS OF THE BODOS AND PARTICIPATION OF WOMENFOLK - Swargiary, Dr Bibungsar Swargiary (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The Bodos are the early settler of North-east India basically Assam and also inhabitants of neighboring countries of India like Nepal, Bhutan, and Bangladesh. Racially the Bodo belongs to the Mongoloid stock of the Indo-Mongoloids or Indo-Tibetans. The Bodos are most adventurous in their cultural activities. The Bodos are most close to nature. Hence, the maximum activities are closed to nature and their livelihood also depends on nature. The observation of the socio-cultural activities and their economy depends on nature. The Bodos observe diverse fairs and festivals at different times or seasons before cultivation, during the cultivation, and after the end of the cultivation. During the observation of the fair and festivals, all the people come to enjoy willingly together. The Bodos are very rich in their culture and tradition which are reflected quite in their fairs and festivals. The fair and festivals of the Bodos mostly related to agriculture and allied activities. These fairs and festivals are classified into three types of Seasonal festivals, Agricultural festivals, and religious festivals. In all the fairs and festivals womenfolk have a big contribution or role in Bodo society. The womenfolk are foremost part of the celebration of the fair and festivals of the Bodos.